Smart poster for information delivery services using Near Field Communication (NFC) / Norfazilah Ibrahim - Ibrahim, Norfazilah (2015)
Traditional poster has been developed for advertising and transmission of information. Typically, traditional posters include an element of text and image. Mobile Phones already had various communications options with the external environments before the introduction of NFC. The introduction NFC technology, it refer to data transfer without using cables can be evaluated using wireless communication aspect. Smart Poster for Information Delivery Services Using Near Field Communication (NFC) is developed through a combination of traditional poster and NFC technology, which to facilitate transmission and retrieval data. It looks like an ordinary poster, but in actual it provides more information services. It can support text, audio, video and picture. All of the information will be stored in NFC tags. Advantage of Smart Poster using NFC technology is it easy to use. By taking the advantage of NFC simplicity of gaining information, user only requires to swipe their mobile phone over the part of Smart Poster that contains NFC tag.